(untitled) (Papeles, 2019)
The value theory is a subject under discussion in economics, and it has not beena salient topic on the leading journals. The present research describes the state-ofartof current research in economic value theory. By bibliometrics, papers of 2019 which aboard this topic, and its references are evaluated, identifying tendences on documentary genre, publishing time-periods, geographical concentrations, JEL codes and Keywords. As final conclusion, the economic theory of value has low importance, is mainly written in English and builded in Europe, with papers of XXI century as favorite source. The references are mainly concentrated in Europe and United States and reflect the multiplicity of schools of thought about economic theory of value. The Asian continent is noted as interested on this field, which publishes on its native languages